(untitled) (Bangladesh Journal of Medicine, 2015)
Introduction: Acute hepatitis can result from varied aetiology ranging from hepatitis viruses, autoimmune hepatitis, drugs and alcohol to metabolic disorders like Wilsons disease. Case report: Here we present a young male who presented to us with classic features of acute hepatitis including prodrome and on evaluation was diagnosed as a case of acute Wilsons disease. Conclusion: In Bangladesh and in most parts common causes of acute hepatitis include hepatitis viruses, alcohol and drugs. However less common aetiologies like Wilsons disease must be kept in mind and looked for, wherever there is strong suspicion. Otherwise many may be denied of potential cure. Bangladesh J Medicine Jul 2015; 26 (2) : 76-78